(untitled) (Stato, Chiese e pluralismo confessionale, 2025)
Public order and religious family rights. Sustainability and limits of an evolving legal relationship The evolution of the public order clause in the nexus between civil and religious legal systems assumes particular significance when contemplated within the context of personal statutes of family law, particularly within Islamic tradition. In addition to its historically function as an instrument for the protection of state sovereignty and a guarantee of respect for the inviolability of fundamental principles, recent developments have enhanced the capacity of public order to mediate between different visions of personal relations within multicultural societies. In this dynamic, the not always univocal solutions expressed by recent jurisprudence of legitimacy denote an ever changing use of the substantial and procedural public order. The reference to the evaluation of the effects of the specific case does not, however, seem to diminish the need to define public order in relation to the protection of the most vulnerable subjects from the effects deriving from the introduction, or blocking, of those legal institutions of family law that involve them. SOMMARIO: 1. Introduzione. La clausola di ordine pubblico alla prova, tra diritto internazionale privato e diritti religiosi - 2. La questione della circolazione dei modelli confessionali e la limitazione posta dalla clausola dell’ordine pubblico. Il paradigma dei rapporti con l’ordinamento canonico - 3. La clausola di ordine pubblico di fronte agli istituti giuridici di diritto familiare islamico: tra interpretazione attenuata e pragmatismo - 4. Il ruolo della giurisprudenza in ordine all’istituto del ripudio islamico. Cenni introduttivi - 5. Ordine pubblico e ripudio islamico: un’analisi delle più recenti pronunce - 6. Kafala e poligamia ovvero l’ordine pubblico di fronte a possibili aperture ermeneutiche. Punti di forza e criticità - 7. Osservazioni conclusive.